Performing ICSI within 4 hours after denudation optimizes clinical outcomes in ICSI cycles - Yini Zhang; Yongzhuang Ma; Zishui Fang; Shiqiao Hu; Zhou Li; Lixia Zhu; Lei Jin (Reproductive Biology and Endocrinology, 2020)
Abstract Background The study aimed to investigate whether and how general and partial time intervals between processes, from human chorionic gonadotrophin (HCG) trigger to intracytoplasmic sperm injection (ICSI), affected the laboratory and reproductive outcomes in ICSI cycles. Methods This was a retrospective data analysis of 3602 women who underwent ICSI treatment cycles using partner or donor sperms, performed at Reproduction Medicine Center of Tongji Hospital of Tongji Medical College of Huazhong University of Science and Technology (Wuhan, China) between October 2016 and September 2018. The clinical pregnancy rate was the major outcome in the study. The fertilization and available embryo rates were secondary outcomes. Results Data from 3602 consecutive fresh ICSI cycles was analysed. Multivariate linear regression and logistic regression analysis of factors related to fertilization and clinical pregnancy rates showed that fertilization rate (P = 0.001) and clinical pregnancy rate (P = 0.037) were significantly associated with denudation (DN)-ICSI interval. Long DN-ICSI interval was associated with higher rate of fertilization than short DN-ICSI interval but significantly decreased clinical pregnancy rate when the interval is over 4 h (P < 0.05). Conclusions DN-ICSI time interval can act as an independent predictor for clinical outcomes in ICSI cycles. The optimal time for ICSI is within 4 h after oocyte denudation for excellent laboratory and reproductive outcomes in ICSI cycles.